Advanced imaging of a histologically confirmed bone infarction of the distal tibia in a Warmblood mare. (13th September 2020) - Hann, M. J.; Rocchigiani, G.; Verin, R.; Milner, P.; Robinson, C.; Castro Martins, M.
Summary: An 8‐year‐old Warmblood‐cross mare presented for investigation of acute onset left hindlimb lameness. Nuclear scintigraphy identified a marked, focal, increase in radiopharmaceutical uptake in the distal aspect of the left tibia. Radiography revealed a large, oval, multi‐loculated radiolucent area within the medulla of the distal metaphysis of the left tibia. The mare was treated conservatively for 6 months but showed little improvement in the lameness so the owner elected for euthanasia. Post‐mortem computed tomographic imaging revealed a large, oval, hypoattenuating area within the distal tibia, surrounded by a thick, irregular, sclerotic border. The lesion occupied the majority of the medullary cavity but the cortical bone was unaffected. Gross and histopathological examination confirmed a diagnosis of a bone infarction in the medullary cavity of the distal tibia.